2018
DOI: 10.3389/fmicb.2018.00182
|View full text |Cite
|
Sign up to set email alerts
|

The Composition and Structure of Biofilms Developed by Propionibacterium acnes Isolated from Cardiac Pacemaker Devices

Abstract: The present study aimed to understand the biofilm formation mechanism of Propionibacterium acnes by analyzing the components and structure of the biofilms. P. acnes strains were isolated from the surface of explanted cardiac pacemaker devices that exhibited no clinical signs of infection. Culture tests using a simple stamp culture method (pressing pacemakers against the surface of agar plates) revealed frequent P. acnes colonization on the surface of cardiac pacemaker devices. P. acnes was isolated from 7/31 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Considering the diffusion barrier limit imposed by the EPS in the biofilms, the protection provided is intrinsincally linked to its biochemical composition as examplified by the interactions between gentamicin and alginate, the major component of mucoid P. aeruginosa biofilms [58]. Variations in the components ensuring the structural integrity of biofilms formed by different isolates of a bacterial strain such as S. aureus [47,59] or Propionibacterium acnes [60] were previously reported. Accordingly, the heterogeneous composition of biofilms formed by F. novicida or F. philomiragia observed here is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the diffusion barrier limit imposed by the EPS in the biofilms, the protection provided is intrinsincally linked to its biochemical composition as examplified by the interactions between gentamicin and alginate, the major component of mucoid P. aeruginosa biofilms [58]. Variations in the components ensuring the structural integrity of biofilms formed by different isolates of a bacterial strain such as S. aureus [47,59] or Propionibacterium acnes [60] were previously reported. Accordingly, the heterogeneous composition of biofilms formed by F. novicida or F. philomiragia observed here is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining with α-dsDNA combined with CLSM also revealed the existence of long filaments of eDNA in biofilms formed either by Enterococcus faecalis (45) or Haemophilus influenzae ECM (46). Moreover, the presence of eDNA-containing fibrous structures in the ECM of Staphylococcus aureus and Propionibacterium acnes biofilms has also been reported using α-dsDNA and atmospheric scanning electron microscopy (47, 48). The use of different technical approaches reinforces the idea that the fibrous assemblies of eDNA observed in some bacterial biofilms actually exist and also offers a novel perspective of the ECM structure of pneumococcal biofilms.…”
Section: Discussionmentioning
confidence: 88%
“…It is most widely recognized as contributing to the pathogenesis of acne, while less appreciated in the pathogenesis of other conditions. The ability of C. acnes to form biofilms may be its most recognized virulence factor, as it can colonize artificial substrates [ 3 ]. It has been recently suggested that lysis of bacterial cells and release of cytoplasmic contents facilitate the formation of their biofilm [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of C. acnes to form biofilms may be its most recognized virulence factor, as it can colonize artificial substrates [ 3 ]. It has been recently suggested that lysis of bacterial cells and release of cytoplasmic contents facilitate the formation of their biofilm [ 3 ]. Biofilm production may have been an important factor in the case presented, as the patient continued to have several positive blood cultures over the course of 4 years that were incompletely treated with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation